Security tensions between South Korea and China : a case study of the impact of overlapping Air Defence Identification Zones - Michálková, Barbora; Dubský, Zbyněk, 1974-; Rod, Zdeněk; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor’s thesis examines the growing security tensions between South Korea and China in the context of their overlapping Air Defence Identification Zones (ADIZ). The analysis is grounded in a realist framework and employs concepts of national security, security dilemma and grey zone operations to interpret state behaviour. The impact and significance of the ADIZ overlap are assessed through a qualitative analysis of international legislation and national regulations, official government publications like the Defence White Papers, and official governmental communication. To further guide the inquiry, two research questions were formulated: How have the overlapping Air Defence Identification Zones threatened South Korean national security? and How has the overlap of Air Defence Identification Zones impacted the bilateral diplomatic relations? The finding demonstrates that the legal ambiguity of ADIZs, combined with China’s asymmetric capabilities and military practices, contributed to South Korea’s heightened sense of vulnerability. Not only that, but at the diplomatic level, it revealed divergent expectations within the relationship and affected the mutual trust.
Vedoucí práce: Zbyněk Dubský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses